Telehealth and Virtual Nurse Teams: Literature Review - Alharbi, Ahlam Zainalabdeen (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Telehealth has changed health care access, especially with the implementation of virtual nurse teams who use technology to provide remote healthcare management. This literature review explores more recent literature (2018-2024) related to telehealth management and virtual nurse teams and discusses the impacts of telehealth and virtual nurse teams related to patient outcomes, access to healthcare, and nursing practice. It includes the historical growth of telehealth, the use of telehealth for chronic disease management, mental health, critical care, and the involvement of virtual nurse teams to assist in the better delivery of care. Subsequent studies show how telehealth increases access to care, lowers health care costs, and increases patient satisfaction, while also discussing the barriers to telehealth that still exist, which include limited training, technology issues, and the lack of regulation. The literature found that virtual nurse teams are effective in-service and monitoring patients, but have barriers to implementation, such as resistance to change and privacy concerns. Data suggests that there are limitations of nurse-led telehealth interventions from a systematic literature review; there were also issues of developing standardized training and acceptance of telehealth interventions. Future research should explore the best use of the telehealth space, address health care access disparities, and, if possible, try to make changes to standardized telehealth practices to ensure equitable access to all clients. This review presented how telehealth and virtual nurse teams can transform health care systems.